2015
DOI: 10.1016/j.neuron.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

The Intracellular Domain of the Frazzled/DCC Receptor Is a Transcription Factor Required for Commissural Axon Guidance

Abstract: Summary In commissural neurons of Drosophila, the conserved Frazzled (Fra)/Deleted in Colorectal Cancer (DCC) receptor promotes midline axon crossing by signaling locally in response to Netrin and by inducing transcription of commissureless (comm), an antagonist of Slit-Roundabout midline repulsion, through an unknown mechanism. Here, we show that Fra is cleaved to release its intracellular domain (ICD), which shuttles between the cytoplasm and the nucleus, where it functions as a transcriptional activator. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 90 publications
3
50
0
Order By: Relevance
“…The ap neurons express low levels of fra (see below), do not express isl (Thor and Thomas, 1997; and data not shown), and do not cross the midline. Fra over-expression causes ectopic midline crossing of ap axons (Neuhaus-Follini and Bashaw, 2015; O ‘Donnell and Bashaw, 2013). We found that over-expression of Isl with ap-Gal4 produces high levels of midline crossing, phenocopying the effect of Fra over-expression (Figure 2F,H).…”
Section: Resultsmentioning
confidence: 99%
“…The ap neurons express low levels of fra (see below), do not express isl (Thor and Thomas, 1997; and data not shown), and do not cross the midline. Fra over-expression causes ectopic midline crossing of ap axons (Neuhaus-Follini and Bashaw, 2015; O ‘Donnell and Bashaw, 2013). We found that over-expression of Isl with ap-Gal4 produces high levels of midline crossing, phenocopying the effect of Fra over-expression (Figure 2F,H).…”
Section: Resultsmentioning
confidence: 99%
“…We observed this interaction in a number of different backgrounds, first with the Fra dominant negative (FraΔC), as well as with the fra and NetAB mutants, and then most dramatically with the sema-1a, fra or NetAB; sema-1a double mutants. Our lab previously uncovered a Netrin-independent role for Fra as well as a role for Robo2 in promoting midline crossing (Evans et al, 2015; Neuhaus-Follini and Bashaw, 2015b; Yang et al, 2009). Both of these pathways function by negatively regulating Robo1 repulsion at the midline.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence supports the concept that specific aspects of neuronal morphogenesis may be controlled by dynamic transcriptional feedback programs in response to transmembrane receptor signaling at growth cones or synapses (Bao et al, 2004;Yang et al, 2009;Neuhaus-Follini & Bashaw, 2015). For example, the axon guidance receptor Frazzled (Fra), which is the Drosophila homologue of DCC and expressed in neuronal growth cones, was shown to be cleaved by c-secretase releasing its intracellular domain (Neuhaus-Follini & Bashaw, 2015).…”
Section: Functions Of Dscam-dependent Membrane-to-nucleus Signaling Imentioning
confidence: 99%
“…The Fra ICD translocates to the nucleus where it functions as a transcriptional activator regulating the expression of commissureless in vivo (Yang et al, 2009;Neuhaus-Follini & Bashaw, 2015). Commissureless on the other hand is a factor controlling midline crossing by negatively regulating the amount of repulsive Robo receptors at the cell surface of precrossing commissural axons (Yang et al, 2009;Neuhaus-Follini & Bashaw, 2015). Here we show that nuclear enrichment of the DSCAM ICD leads to transcriptional up-regulation of the repulsive axon guidance receptor Unc5a as well as down-regulation of the neurotrophin receptor Ntrk2 in primary neuron cultures.…”
Section: Functions Of Dscam-dependent Membrane-to-nucleus Signaling Imentioning
confidence: 99%